Pre-analytics, a national survey of Senonetwork Italia breast centers: Much still to do ahead. Issue 2 (February 2021) - Costarelli, Leopoldo; Rizzo, Antonio; Bortul, Marina; Pietribiasi, Francesca; Taffurelli, Mario; Tinterri, Corrado; Cataliotti, Luigi; Burlizzi, Stefano; Bargiacchi, Lavinia; Fortunato, Lucio; ,
Abstract: Introduction: Pre-analytics involves handling and processing of microbiopsy and surgical specimen. It is critical for the preservation of morphology and the integrity of molecular markers, which are paramount as prognostic and predictive factors in breast cancer. Although pre-analytical variables in breast cancer are codified by national and international guidelines, there is currently no data on their actual endorsement in clinical practice among Breast Units (BU). Materials and methods: An anonymous questionnaire was sent by e-mail by Senonetwork Italia, a no-profit organization representing the multidisciplinary network of BU in Italy. The questionnaire involved twenty-four questions concerning critical issues related to the average time and transport temperature of the samples, monitoring of warm and cold ischemia, average fixation time for biopsies and surgical specimens, inking of the margins, and radiography of the operating sample. Results: Forty-nine of 113 affiliated BU (43%), involved in the management of 44% of all breast cancer treated every year in Italy, answered the questionnaire. More than 90% of the BU reported a biopsy/VABB fixation time between 6 and 24 h. Only 41% of the Centers received the fresh operative sample to be sectioned immediately, 20% used the vacuum method and the sample arrived in the laboratory within 24–72 h. Delay in sectioning the sample was reported in as many as 40% of BU, while hot and cold ischemia time was monitored in only 4.2% and 6.2% of BU, respectively. Conclusion: Critical issues on pre-analytics are reported by the majority of dedicated BU in Italy. This represents a major challenge regarding quality of care, and improvements are needed in order to obtain valid and reproducible results of prognostic and predictive factors.